ISLAMIC DIGITAL TRANSFORMATIONAL LEADERSHIP: A CONCEPTUAL RECONSTRUCTION OF EDUCATIONAL MANAGEMENT IN THE DIGITAL ERA - Hidayat Mustafid (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Digital transformation has brought significant changes in the management and leadership systems of education, including in Islamic educational institutions. The development of digital technology requires Islamic educational institutions to be able to build adaptive, innovative, and technology-based organizational governance without losing their spiritual identity and Islamic values. However, the transformational leadership model that has been used in education management is still considered to have limitations because it is more oriented to organizational effectiveness and has not integrated the spiritual dimension and digital governance comprehensively. This research aims to reconstruct transformational leadership in the management of Islamic education in the digital era through the integration of spiritual leadership and digital governance. The research uses a conceptual model-based Systematic Literature Review (SLR) approach by analyzing various relevant scientific articles, academic books, and international reports in the range of 2000–2025. The analysis was carried out through the stages of identification, selection, synthesis, and interpretation of literature to build a conceptual model of Islamic education leadership in the digital era. The results of the study show that the study of transformational leadership, spiritual leadership, and digital governance is still partially developed and has not been fully integrated in the context of Islamic education. This research produces the